PENGGUNAAN MEDIA SOSIAL SEBAGAI SUMBER PEMBELAJARAN DI SMA: RISIKO DAN PELUANG - I Nyoman Sadwika; Nyoman Astawan; Ni Putu Ari Darmayani; Ni Kadek Dwi Handayani (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
This study examines the use of social media as a learning medium in Indonesian language instruction at the senior high school level by analyzing its opportunities, challenges, and necessary mitigation strategies. Social media has the potential to enhance students’ learning motivation, active engagement, and creativity, while providing access to authentic language resources relevant to real-life contexts. However, its implementation also presents challenges, including learning distractions, the spread of inaccurate information, the decline of standard language usage, violations of academic integrity, and digital ethical issues such as privacy risks and cyberbullying. To address these challenges, this study proposes mitigation efforts encompassing the strengthening of digital and media literacy, systematic integration of social media into learning tasks, the enforcement of ethical guidelines and digital privacy protection, the application of authentic assessments to ensure academic integrity, and the provision of psychosocial support for students. The findings indicate that social media is not merely an alternative tool but a strategic necessity in Indonesian language learning in the digital era, requiring curriculum flexibility and enhanced teacher competencies. Further studies are recommended to explore long-term impacts and pedagogical effectiveness across diverse social contexts.